2013
DOI: 10.1074/jbc.m113.455444
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Regulatory Light Chain (RLC) Phosphorylation Change as a Modulator of Cardiac Muscle Contraction in Disease

Abstract: Background: Cardiac myosin regulatory light chain (RLC) phosphorylation alters cardiac muscle function.Results: Phosphorylation affects mechanical parameters of cardiac muscle contraction during shortening.Conclusion: Phosphorylation impacts mechanical function of cardiac muscle and is altered during cardiac disease.Significance: Understanding RLC regulation by phosphorylation in cardiac muscle contraction is crucial for understanding changes in disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 53 publications
1
95
0
Order By: Relevance
“…Given that the entire load velocity relationship is shifted to greater values, it is not surprising that power output of the individual myosin motor was increased upon phosphorylation. Studies utilizing porcine cardiac fibers showed that increased RLC phosphorylation levels lead to an increase in force and power output during fiber shortening at physiologically relevant loads [45]. A phosphorylation induced increase in the maximum power of isolated myosin shown in this work is likely a contributing factor to this phenomenon.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Given that the entire load velocity relationship is shifted to greater values, it is not surprising that power output of the individual myosin motor was increased upon phosphorylation. Studies utilizing porcine cardiac fibers showed that increased RLC phosphorylation levels lead to an increase in force and power output during fiber shortening at physiologically relevant loads [45]. A phosphorylation induced increase in the maximum power of isolated myosin shown in this work is likely a contributing factor to this phenomenon.…”
Section: Discussionmentioning
confidence: 71%
“…In cardiac muscle fibers, isometric force production increased with increasing levels of RLC phosphorylation during fiber shortening [45]. Interplay between cardiac myosin light chain kinase (MLCK) and a myosin phosphatase holoenzyme in human ventricular tissue is thought to maintain the level of RLC phosphorylation at about ~40% [5,25,30].…”
Section: Introductionmentioning
confidence: 99%
“…[37]. In cardiac muscle, RLC phosphorylation is associated with increased myocardial performance and enhances myosin motility under loaded conditions in vitro [38, 39]. Electron microscopic studies show that the motor domains of unphosphorylated skeletal and cardiac muscle myosin-2 filaments are held in close apposition to the filament backbone with a high degree of order.…”
Section: Regulation By Phosphorylationmentioning
confidence: 99%
“…Higher RLC phosphorylation levels correlate with higher isometric force and power output in permeabilized rat cardiac trabeculae and with heart failure in human tissue (Toepfer et al 2013) implying it is a compensation mechanism for power shortage in failing heart.…”
Section: Natural Myosin Activationmentioning
confidence: 99%